Dimensions on born-global firms' case studies - Pimenta, Ananda Carvalho; Joswig, Marcus; De Miranda Oliveira Junior, Moacir; Sbragia, Roberto (Internext, 2017)
The objective of this research is to analyze which dimensions and attributes are discussed in born-global firms’ case studies presented by the literature and in practice. For these two specific objectives were proposed: i) identify the dimensions used to study the born-global firms; ii) identify the main concepts applied to such dimensions; both analysis are based on cases studies addressed in the literature and practical case studies. This research is classified as exploratory and contains a content analysis. Furthermore, it was based on a selection of academic articles obtained on ISI Web of Knowledge database focusing on born-global firms’ case studies. The results demonstrated that the main issues regarding the born-global firms are developed in an aligned perspective regarding the theory even when the article’s focused on a particular industry. As a contribution, this study presented the list of dimensions and attributes that can be used as a reference for complementary discussions regarding the born-global case studies or even theoretical propositions. The composition of case studies that provides a broad overview for the researchers can be considered as an additional contribution of this article.